FINANCIAL STATEMENT FRAUD DETECTION USING THE BENEISH M-SCORE AND ITS IMPLICATIONS FOR FIRM VALUE: A NARRATIVE LITERATURE REVIEW - Shukurulloxon Mutalibov; Elis Mediawati; Mimin Widaningsih (Journal of Development Economics and Digitalization, Tourism Economics, 2026)
Financial statement fraud remains a major concern for investors, regulators, and researchers because it reduces the reliability of financial reporting and can lead to significant economic losses. Among the various approaches developed to detect such fraud, the Beneish M-Score has become one of the most widely used tools due to its practicality and reliance on publicly available financial data. This study reviews the existing literature on the use of the Beneish M-Score in detecting financial statement fraud and examines the implications of such fraud for firm value. Using a narrative literature review approach, this article synthesizes prior theoretical and empirical studies related to fraud detection, earnings manipulation, and market responses to fraudulent financial reporting. The review shows that the Beneish M-Score is a useful initial screening tool for identifying potential earnings manipulation, although its effectiveness varies across countries, industries, and regulatory environments. The literature also indicates that financial statement fraud generally has a negative effect on firm value through declining investor confidence, falling stock prices, reputational damage, and higher costs of capital. Overall, this study highlights the importance of early fraud detection and emphasizes that the Beneish M-Score can provide meaningful insights when used alongside other analytical approaches and supported by strong corporate governance. Keywords: financial statement fraud; Beneish M-Score; firm value; earnings manipulation; narrative literature review